Ajaran Kepanditaan Dalam Lontar Bubuksah Sebagai Upaya Untuk Memahami Hakikat dan Tujuan Hidup (Suatu Tinjauan Filosofis) - I Made Jaya Negara S.P; Dian Syanita Utami Dewi; Untung Suhardi (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Lontar Bubuksah as a creation or the heritage of Hindu culture contains a story about the moral preaching of priests, philosophy of life and syncretism between the preaching of Shiva and Budha thus it is clear that the manuscript contents of the Lontar Bubuksah are about religion. Through the two main figures of Gagakaking and Bubuksah brothers each chose a different path in realizing their ideals.Even the way carried out each seemed very contradictory. However, both of them hold one concept that is successfully believed and implemented consistently and consequently The value of holiness is played by the character of Gagakaking with all his behavior based on spiritual purity. While the value of lascarya is played by Bubuksah in his tyaga pati and all manner of behavior in carrying out his brata bherawa. Different behaviors have a connecting line that can be drawn is the value of a satya; loyalty to the choice of beliefs that are considered true with all the consequences, as well as being faithful to both achieve the realm of freedom (moksa). This research uses a qualitative research method about the Bubhuksah lontar text. Therefore, from the research standpoint it is an exploratory research (explotrative research) in this case the research and study of the Bubuksah lontar text with primary data namely the Bubuksah lontar and secondary data of this study were obtained from two sources namely documents and through discussions with informants and in the form of literature, references and books.Keywords: Phylosophy, preaching of priests, Lontar Bubuksah and Gagakaking, goal of life.